2021
DOI: 10.3390/ijerph19010286
|View full text |Cite
|
Sign up to set email alerts
|

On the Move or Barely Moving? Age-Related Changes in Physical Activity, Sedentary, and Sleep Behaviors by Weekday/Weekend Following Pandemic Control Policies

Abstract: This study examined pre-pandemic (2017-early March 2020) to early-pandemic (Spring 2020) changes in moderate-to-vigorous PA (MVPA), light PA (LPA), and sedentary behavior/sleep (SS), by weekday/weekend, and age (preschool, elementary, middle school). We re-enrolled children from two pre-pandemic obesity prevention trials and examined differences in accelerometer-measured PA from pre-pandemic to early-pandemic across age groups using linear mixed models. Children (n = 75) were 51% multiple race/ethnicities, 29%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Previous research suggests that 110–165 daily excess calories result in excess weight gain over a 10 year period among US children [ 17 ]. Recent evidence also suggests that children may have been less physically active and engaged in more sedentary behavior during school closures, which may further exacerbate concerns about unintended weight gain [ 16 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that 110–165 daily excess calories result in excess weight gain over a 10 year period among US children [ 17 ]. Recent evidence also suggests that children may have been less physically active and engaged in more sedentary behavior during school closures, which may further exacerbate concerns about unintended weight gain [ 16 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 14 articles (29, 33,39,40,43,44,48,50,55,58,61,62,64,66) reported the relationship between PA and psychological and/or behavioral problems during the COVID-19 pandemic (Table 2). To measure the PA levels, ten studies (29, 33, 40, 43, 44, 50, 58, 62, 64, 66) used a self-designed questionnaire, three studies adopted a validated questionnaire including the International Physical Activity Questionnaire Short Form (IPAQ-SF) (48,55) and Goldin-Shepard Leisure-The Physical Activity Questionnaire (61), and one study utilized an accelerometer (39).…”
Section: Relationship Between Pa and Psychological And/or Behavioral ...mentioning
confidence: 99%
“…Overall, 14 articles (29, 33,39,40,43,44,48,50,55,58,61,62,64,66) reported the relationship between PA and psychological and/or behavioral problems during the COVID-19 pandemic (Table 2). To measure the PA levels, ten studies (29, 33, 40, 43, 44, 50, 58, 62, 64, 66) used a self-designed questionnaire, three studies adopted a validated questionnaire including the International Physical Activity Questionnaire Short Form (IPAQ-SF) (48,55) and Goldin-Shepard Leisure-The Physical Activity Questionnaire (61), and one study utilized an accelerometer (39). To identify the occurrence of psychological and/or behavioral problems, nine studies (29, 33, 40, 43, 44, 58, 62, 64, 66) used a self-designed questionnaire where 5 studies employed a validate questionnaire such as the simplified Chinese Profile of Mood Status (POMS) (48), Depression, Anxiety, Stress Scale-21 (DASS-21) (39), The Psychological Distress Index (50), 9-Items Patient Health Questionnaire (PHQ-9) (55) and Generalized Anxiety Disorder Scale (GAD-7) (55), and Brief Symptom Inventory (BSI) (61).…”
Section: Relationship Between Pa and Psychological And/or Behavioral ...mentioning
confidence: 99%
“…Regarding Hypothesis 1 (i.e., guideline adherence would differ significantly in several demographics), our findings only supported significant differences in age, gender and grade, yet not in parents’ education level and household income. Age-related declines in MVPA, increases in ST and lower sleep duration in children have been demonstrated by previous evidence [ 2 , 50 ]. The relationship may be from the increased time that is required for academia as one progresses through school [ 2 , 51 ].…”
Section: Discussionmentioning
confidence: 57%
“…However, another national survey, of Korean children, revealed that decreased sleep duration was significantly associated with increased risks in the highest quartile of PBF and the lowest quartile of skeletal muscle index in boys, and there was no significant association between sleep duration and obesity parameters, except waist circumference in girls [ 58 ]. The above findings imply the need for more examinations on the relationship between sleep and weight-related outcomes in children, especially taking the multidimensional components of sleep (e.g., patterns, quality) into account [ 50 , 59 ]. However, this is likely a less imperative target than PA and ST, given the mixed findings.…”
Section: Discussionmentioning
confidence: 99%